2014
DOI: 10.1371/journal.ppat.1004521
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Activation in Human Hantavirus Infection Explained by Virus-Induced IL-15/IL15Rα Expression

Abstract: Clinical infection with hantaviruses cause two severe acute diseases, hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS). These diseases are characterized by strong immune activation, increased vascular permeability, and up to 50% case-fatality rates. One prominent feature observed in clinical hantavirus infection is rapid expansion of natural killer (NK) cells in peripheral blood of affected individuals. We here describe an unusually high state of activation of such expanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 61 publications
(74 reference statements)
4
56
0
4
Order By: Relevance
“…However, the host has evolved mechanisms to counteract pathogen immune evasion and ensure protective immunity that involve upregulation of the expression of IL-15 and non-classical MHC molecules. Intracellular pathogens such as mycobacteria 128 , listeria 129 , Cryptosporidium parvum 130 and a wide range of viruses 89,131133 have been reported to induce IL-15 expression, probably downstream of the activation of various innate immune receptors such as TLR4 (REFS 81,133). Furthermore, intracellular pathogens have been reported to upregulate the expression of non-classical MHC class I ligands for activating NK receptors on host cells.…”
Section: Role Of Il-15 In Health and Diseasementioning
confidence: 99%
“…However, the host has evolved mechanisms to counteract pathogen immune evasion and ensure protective immunity that involve upregulation of the expression of IL-15 and non-classical MHC molecules. Intracellular pathogens such as mycobacteria 128 , listeria 129 , Cryptosporidium parvum 130 and a wide range of viruses 89,131133 have been reported to induce IL-15 expression, probably downstream of the activation of various innate immune receptors such as TLR4 (REFS 81,133). Furthermore, intracellular pathogens have been reported to upregulate the expression of non-classical MHC class I ligands for activating NK receptors on host cells.…”
Section: Role Of Il-15 In Health and Diseasementioning
confidence: 99%
“…Each hantavirus is antigenically distinct and maintained within single or at most a few rodent or insectivore hosts, but are infectious for other hosts. The main research complication from natural infection is the zoonotic risk and potentially subclinical effects on the immune response associated with viral defenses such as CD8 + T cell (Taruishi et al, 2007) and NK function as demonstrated in human studies (Braun et al, 2014). Several hantaviruses are zoonotic and may cause severe disease in humans.…”
Section: )mentioning
confidence: 99%
“…We believe that these adaptive NK cells are induced by CMV specifically and are not induced by other pathogens. Although others have suggested that NKG2C + NK cells are associated with the hantavirus in Sweden and the chikungunya virus in Africa, all of the patients participating in these studies were also co‐exposed to CMV, suggesting that the NKG2C + NK cells were caused by CMV infection rather than infection with other viruses (Braun et al, ; Petitdemange et al, ). To further highlight the specificity of CMV‐induced adaptive NK cells, recent studies have shown that CD57 + NKG2C + NK cells are not expanded in response to Epstein–Barr Virus (EBV) and that human HSV‐2 infection did not induce adaptive NK cells (Björkström, Svensson, Malmberg, Eriksson, & Ljunggren, ; Hendricks et al, ).…”
Section: Discovery Of Viral‐induced Adaptive Nk Cellsmentioning
confidence: 91%